Synthesis, physicochemical characterization of ZnO and α-MoO3/ ZnO heterostructures and their photocatalytic activity for the methylene blue (MB) dye degradation - Ibrahim, Yusuf; Abdullah, Abdul Halim; Abdul Rashid, Suraya; Muhamad, Ernee Noryana (Elsevier, 2023)
This research fabricated a hybrid of α-MoO3/ZnO heterostructures via ultrasonic-assisted hydrothermal synthesis and evaluated its photocatalytic activity by degradation of Methylene Blue dye (MB) under visible light irradiations. The physicochemical properties of the heterostructure were characterized using several solid-state characterization techniques. Which indicated that with the addition of α-MoO3, there is a change in morphology from ZnO hexagonal to anorthic nanorods, then gradual to a rod like shape. The α-MoO3/ZnO in the ratio of 2:1 (MZ-21) exhibited a faster MB degradation rate of 0.411 min−1, which is three times faster than that of the ZnO nanoparticle. Various parameters, such as catalyst dosage, initial MB concentration, and pH, were varied to determine the optimum condition for the MB degradation. The photodegradation percentage for α-MoO3/ZnO (MZ21) of 99 is higher than that of ZnO (53), suggesting that the addition of MoO3 to the hybrids enhanced the degradation efficiency. The photodegradation process follows pseudo-first-order kinetics. The radical scavenger's influence on MB degradation provides insights into the MB degradation mechanism. The dominant species that contributed the highest effect toward MB degradation were the OH radical, followed by .O2− radical species, signifying that they are the species largely responsible for the attack of MB dye molecules. The reusability studies revealed that the hybrid photocatalyst could be repeatedly used up to four times without severe deactivation, indicating the excellent reliability of the hybrid.